KRAS-mutated non-small cell lung cancer: new therapy strategies - K. K. Laktionov; K. A. Sarantseva; L. A. Nelyubina; S. V. Gamayunov; E. A. Kolesnikova; M. G. Gordiev (Сибирский онкологический журнал, 2024)
Lung cancer remains one of the most dangerous and most common cancers, requiring constant improvement of diagnostic and treatment methods. The genetic heterogeneity of lung cancer forces us to search for new therapeutic targets in an attempt to achieve greater effectiveness for certain groups of patients. The purpose of the study was to update current knowledge about lung adenocarcinoma with a mutation in the KRAS gene, to consider new opportunities for personalized treatment of KRAS-mutated NSCLC and to form an image of a Russian patient who is potentially indicated for targeted therapy. Material and methods. A search of available literature sources published in the Pubmed, Cochrane Library, Elibrary database was carried out, publications covering the period from 2008 to 2023 were included. Results. The article discussed molecular genetic testing, including NGS next generation sequencing, and its role in determining the presence of KRAS gene mutations in patients with lung cancer. the effectiveness of targeted drugs, such as Sotorasib and Adagrasib was also discussed. The mechanism of action is aimed at suppressing the activity of the mutant KRAS G12C protein, which can significantly improve patient survival prognosis. We obtained data on the results of testing 935 patients with non-squamous non-small cell lung cancer from various medical centers in Russia. The KRAS gene mutation was identified in 160 (17.1 %) patients, of whom 96 (10.3 %) had KRAS G12C variant. The KRAS mutation was determined by PCR in 44 patients and by NGS (including on the FoundationOne platform) in 111 patients. Clinical characteristics, such as gender, age, smoking status, PD-L1 expression level, presence of co-mutations (TP53, STK11, KEAP1, were largely similar between patients from real-world clinical practice and patients included in the CodeBreak100 study. Conclusion. The research results confirm the high effectiveness of Sotorasib and Adagrasib for patients with the KRAS G12C mutation and open up new prospects in the treatment of lung cancer. The clinical data obtained from Russian patients demonstrate consistency with the patient profile from registration studies of these drugs. This once again demonstrates the need to expand the range of molecular genetic testing for timely identification of this group of patients and prescribing the most effective treatment for them.